INTELLECTUAL INTELLIGENCE, LEARNING BEHAVIOR AND AVAILABILITY OF EDUCATIONAL MEANS ON INTERMEDIATE ACCOUNTING UNDERSTANDING WITH MOTIVATION AS A MODERATING VARIABLE - fitri nuraini (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2019)
Abstract Intermediate Financial Accounting is a continuation of accounting science from basic accounting, the countain in intermediate financial accounting includes riil account accounting treatment and special accounting problems. Concepts in intermediate financial accounting explain accounting treatment including recognition, measurement, statement and disclosure. This study examines the influence of intellectual intelligence, accounting behavior and availability of educational facilities on the understanding of intermediate financial accounting with motivation as a moderating variable. The sampling technique used convenience sampling with a sampling of 43 students. The study uses the Moderated Regression Analysis (MRA) analysis tool. The results showed that (1) intellectual intelligence, learning behavior and the availability of educational facilities had no significant effect on the understanding of intermediate financial accounting, (2) motivation to moderate the influence of intellectual intelligence and learning behavior on understanding middle financial accounting, (3) motivation does not moderate the influence of availability educational facilities for understanding middle financial accounting.